Determinación de la influencia de los diferentes ambientes del campus de la ESPAM “MFL” en la comunidad de aves en las distintas épocas del año - Guerrero Jurado, Juana Paulina (2016)
The objective of the study was to characterize species of birds in distinct habitats of the Escuela Superior Politécnica Agropecuaria in Manabí, Ecuador in the wet and dry seasons, between April and October of 2015. Sampling occurred in 23 listening stations in 4 previously identified habitats: pastures, farmland of corn, cocoa, coffee, and teak, wetlands, and populated areas. Pastures and farmlands of cocoa and coffee had the highest abundance of birds, while wetlands and populated areas had the lowest abundance. However, there was no difference in species richness of birds across the 4 habitat types, it which means that the variety of species found in the environment 1 is similar to the variety of species found in the environment 2 or 3. The conservation status of observed species was also determined on a scale of one to ten, with one signifying species not present on the red list (e.g., Furnarius leucopus/Hornero del Pacífico) while species with values from two to ten being listed on the Red List of Ecuadorian Birds (e.g., Anhima cornuta/Gritador Unicornio). Eighty species of birds, with a total of 1390 individuals were identified across both seasons, with the dry season having a higher amount of individuals (766), which could be due to the higher availability of resources.